Penyuluhan Stunting : Upaya Meminimalisir Tingginya Angka Stunting di Desa Sawidago: Penyuluhan Stunting : Upaya Meminimalisir Tingginya Angka Stunting di Desa Sawidago - Puspita Dewi, Niluh; mariyani, mariyani; Alaydrus, Syafika; Anggi, Viani; Magfirah, Magfirah; Kurnia Utami, Indah (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2023)
Indonesia has quite a serious nutritional problem which is characterized by many cases of malnutrition. Malnutrition is an impact of nutritional status. Stunting is a condition of malnutrition that is related to past nutritional deficiencies, so it is a chronic nutritional problem. Many factors can cause stunting in toddlers, such as toddler characteristics and socio-economic factors. Community outreach activities are carried out with the aim of providing education to the public regarding the risk factors for stunting and its prevention. This counseling was carried out in order to increase the knowledge of the residents of Sawidago Village, especially mothers, because the mother is the person who is always with the child from pregnancy to 24 months of age. So that the baby's development will continue to be assisted by the mother. Counseling is provided using an interactive lecture method through posters and distribution of leaflets as well as social service. The effectiveness of the extension was tested by administering a partner satisfaction questionnaire with the activities carried out. The results of activity observations showed that Partners were satisfied with the outreach activities carried out.